Desenvolvimento de software para exibição de exames de eletrocardiograma - Otero, Eduardo Gomes Lamas [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The main objective is to create a software, using C++ language, for reading and exhibiting in a graphic an Electrocardiogram (ECG) wave. The data is recorded as a FM modulated signal and compressed using Adaptive Differential Pulse Code Modulation (ADPCM). The signal have this characteristics because it was acquired using an experimental equipment, this equipment is the result of research made by the professor who supervised this work. FM demodulation techniques in discrete time, discrete filters and digital signal processing are some of the topics that can be found in this essay. Some concepts about the human heart and about ECG waves are also briefly introduced. These concepts are necessary for understanding the final evaluation of the software performance. The development is partly made using MATLAB. Most of the functions that are used on the software are first tested and designed in MATLAB environment. In the end, an evaluation is done comparing the results that are expected with the ones that MATLAB presents and the ones that the developed software presents

Este trabalho trata do desenvolvimento de um software, em linguagem C++, para leitura e representação gráfica de arquivos contendo informações referentes a exames de Eletrocardiograma (ECG). A informação de interesse está gravada em um sinal modulado em FM e comprimido por um algoritmo comum em telecomunicações (o ADPCM). O sinal de ECG tem essas características por ter sido gerado por um equipamento experimental, fruto de pesquisa realizada pelo docente orientador deste trabalho. No desenvolvimento são abordadas técnicas de demodulação FM em tempo discreto, filtros discretos e processamento digital de sinais de um modo geral. Também são abordados, de forma mais breve, tópicos necessários para o reconhecimento básico de um ECG e suas características. O desenvolvimento do software se dá em paralelo com simulações no MATLAB, com a finalidade de ilustrar as ferramentas utilizadas e os passos necessários para a recuperação do sinal de ECG. Por fim é feita uma avaliação geral do software desenvolvido e futuros desenvolvimentos são apontados para melhorar o desempenho e corrigir defeitos do programa
Keywords: Processamento de sinais - Tecnicas digitais; Software - Desenvolvimento